L’intégration internationale du Royaume-Uni post-Brexit : vers une reconfiguration de la régionalisation ? - Mark Bailoni (Belgeo)
While the United Kingdom prepares to leave a weakened European Union, Brexit could mean a new stage in regionalisation in Europe, indeed in the world. If until then the major geopolitical processes went towards more regional integration, the United Kingdom could not follow this way. The Commonwealth has been widely promoted by Brexit leaders as the space in which the United Kingdom could politically and economically flourish after leaving the EU. The British strategy of international integration therefore seems to change scale and spatial references. By a critical geopolitical approach, this paper aims to question the contemporary definition of the Commonwealth and its relation to the concept of regionalisation, and analyse the feasibility of the Brexiters’ international strategy.